Minutes (extract)
017a-0053-001 Extract from N.C.L. Minutes 21st June 38. (e) Political Situation: Discussion took place upon the existing situation in Spain, and the rumours regarding the possibility of an armistice. It was reported that the Parliamentary Labour Party was to initiate a Debate in the House of Commons that day, when the opportunity would be taken on the Foreign Office Vote to raise the question of the bombing of British ships and the bombing of Spanish civilians. (It was also intended that reference should be made to the situation in China.) 292/946/17a/53